Answer:
44
Step-by-step explanation:
6x +22 + 7x + 16 = 90
13x +38 =90
13x = 52
x = 4
7 x 4 +16 = 44
Answer:
(x - 2)(5x + 3) = 0
Step-by-step explanation:
5x² - 7x - 6 = 0
Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term.
product = 5 × - 6 = - 30 and sum = - 7
The factors are - 10 and + 3
Use these factors to split the x- term
5x² - 10x + 3x - 6 = 0 ( factor the first/second and third/fourth terms )
5x(x - 2) + 3(x - 2) = 0 ← factor out (x - 2) from each term
(x - 2)(5x - 3) = 0 ← in factored form
Answer:
the answer is number three
Good evening ,
___________________
Step-by-step explanation:
Look at the photo below for the answer.
:)